2017
DOI: 10.5152/turkpediatriars.2017.4187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pulmonary functions in preschool children born late-preterm

Abstract: Aim: The aim of this study was to evaluate the pulmonary functions of preschool children born late-preterm. Material and Methods:Children aged between 3-7 years who were born at 34 0/7 -36 6/7 weeks' gestation represented the target sample. Patients with a diagnosis of congenital cardiac, pulmonary and/or muscle diseases were excluded. Respiratory symptoms were evaluated using the modified asthma predictive index and International Study of Asthma and Allergies in Childhood criteria for children aged under and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The frequency of allergic diseases such as bronchial asthma, allergic rhinitis and atopic dermatitis is increasing both in our country and in many countries of the world [4][5][6]. It was determined that the lung functions of pretermborn children decreased significantly at school age [7][8][9][10]. In addition, various studies investigating atopy in premature children have been conducted, some studies have shown that atopy is a reduced risk factor, while others have shown that there is no relationship between gestational age and atopy [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of allergic diseases such as bronchial asthma, allergic rhinitis and atopic dermatitis is increasing both in our country and in many countries of the world [4][5][6]. It was determined that the lung functions of pretermborn children decreased significantly at school age [7][8][9][10]. In addition, various studies investigating atopy in premature children have been conducted, some studies have shown that atopy is a reduced risk factor, while others have shown that there is no relationship between gestational age and atopy [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of allergic diseases such as bronchial asthma, allergic rhinitis and atopic dermatitis is increasing both in our country and in many countries of the world [4][5][6]. It was determined that the lung functions of pretermborn children decreased significantly at school age [7][8][9][10]. In addition, various studies investigating atopy in premature children have been conducted, some studies have shown that atopy is a reduced risk factor, while others have shown that there is no relationship between gestational age and atopy [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%